Caracterização do perfil dos consumidores de carne de frango - Cardoso, Angélica Cristina Roque [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Brazil is currently the world‟s largest exporter of chicken meat, but they maintain of this position in the international market requires constant evolution. In the quest for quality improvement, is essential to know the consuming public because the quality translates to meet the customer expectations. So, this study aimed to demonstrate the profile of chicken meat consumers through questionnaire-like interviews in order to generate information that can guide the productive sector in the pursuit of quality and competitiveness. 738 questionnaires were applied in the region of Araçatuba (SP) and 401 questionnaires Barra do Garça (MT), that were filled manually or sent via email by respondents. Of respondents Araçatuba, 40.7% were women and 59.3% men, from Barra do Garça women represented 52.6% and men 47.4%. Most respondents from Araçatuba revealed preference for beef, and from Barra do Garça, for pork. Only about 2% of respondents said they did not enjoy chicken. The economic status of the interviewees influenced the consumption habits of chicken meat. The meat color, the brand of the product and the shelf life requirements are observed at the time of purchase Despite the farm chicken present habitual consumption by households, there is a market, albeit restricted to the production and sale of organic chicken meat. About 66 % of consumers believe that chicken can transmit diseases and 81 % believe that hormones are used in farm chicken production. Based on these results, we conclude that any initiative to improve the quality of the product must be accompanied by enlightening campaigns for consumers.
Keywords: Frango de corte; Consumo; Pesquisa de mercado; Oferta e procura; Carne de ave; Satisfação do consumidor; Demand food